2007
DOI: 10.1017/s1355617707071007
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral effects of HIV-1 infection in China and the United States: A pilot study

Abstract: The HIV epidemic in China has been increasing exponentially, yet there have been no studies of the neurobehavioral effects of HIV infection in that country. Most neuroAIDS research has been conducted in Western countries using Western neuropsychological (NP) methods, and it is unclear whether these testing methods are appropriate for use in China. Twenty-eight HIV seropositive (HIV+) and twenty-three HIV seronegative (HIV−) individuals with comparable gender, age, and education distributions were recruited in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 42 publications
(32 reference statements)
1
51
0
1
Order By: Relevance
“…In addition, HIV-monoinfected and HIV-co-infected subjects experienced reduced employment or work time in the span of a year. These results build on previous studies conducted in China by Cysique et al [51], which demonstrated significant NP deficits in HIV-positive individuals in comparison with HIV-negative controls.…”
Section: Recent Hiv Neurocognitive Studies In Asiasupporting
confidence: 91%
“…In addition, HIV-monoinfected and HIV-co-infected subjects experienced reduced employment or work time in the span of a year. These results build on previous studies conducted in China by Cysique et al [51], which demonstrated significant NP deficits in HIV-positive individuals in comparison with HIV-negative controls.…”
Section: Recent Hiv Neurocognitive Studies In Asiasupporting
confidence: 91%
“…Details of the NP battery selection and adaptation for use in China are provided in Cysique et al (2007a). The NP battery in Mandarin was administered by trained examiners in the local Fuyang dialect, which uses the same written form as the Mandarin, but sometimes is pronounced differently.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is preliminary evidence of NP and electroencephalographic abnormalities being associated with clade C infection in India (Riedel et al, 2006;Sinha & Satishchandra, 2003;Yepthomi et al, 2006). Finally, Cysique et al (2007a) recently reported a small study comparing NP effects of HIV infection (clade B) in China and the U.S. An NP test battery that has been used in large multi-site studies in the U.S. was translated and adapted slightly for cultural relevance to the Chinese population, and was administered to 28 HIV+ and 23 demographically similar HIV − controls in China, as well as to 39 HIV+ and 31 HIV− controls in the U.S.. The test battery was well understood and tolerated by the Chinese participants.…”
Section: Introductionmentioning
confidence: 99%
“…When tests are translated and modified in a culturally and linguistically relevant manner, then the results of neuropsychological assessment of HIV infected persons in non-western settings are beginning to yield similar results to those from North America and Europe. For example, recent preliminary work by Heaton and colleagues (Cysique et al, 2007) shows that norms originally developed in the US could be applied to suitably modified versions of neuropsychological tests in China to demonstrate very similar rates of NP impairment in HIVþ individuals to what has been observed in the United States. Preliminary data involving translations into Marathi (an Indian Other factors that may need to be considered in evaluating the neurocognitive effects of HIV People with HIV infection may have other attributes and conditions that could either exert additive effects on HIV related brain disease, or may make it difficult to disentangle HIV effects from the effects of various confounds.…”
Section: Culturementioning
confidence: 99%